Cultural Adaptation Stress and Social Competence as Determinants of Hopelessness - Chikwe, Chidinma; Piskorz-Ryń, Oriana; Saadati, Seyed Amir (Journal of Psychosociological Research in Family and Culture, 2024)
Objective: The objective of this study was to examine the relationship between hopelessness, cultural adaptation stress, and social competence among international students. The aim was to identify how these factors interact to influence the psychological well-being of this population.Methods: This cross-sectional study involved 430 international students selected through stratified random sampling. Participants completed the Beck Hopelessness Scale (BHS), the Acculturative Stress Scale for International Students (ASSIS), and the Social Skills Inventory (SSI). Data analysis was conducted using SPSS version 27, employing Pearson correlation to explore bivariate relationships and linear regression analysis to investigate the predictive power of cultural adaptation stress and social competence on hopelessness.Results: Descriptive statistics revealed mean scores of 9.45 (SD = 3.27) for hopelessness, 70.34 (SD = 15.62) for cultural adaptation stress, and 80.23 (SD = 12.48) for social competence. Pearson correlation analysis showed significant positive correlations between hopelessness and cultural adaptation stress (r = 0.52, p < 0.001) and significant negative correlations between hopelessness and social competence (r = -0.48, p < 0.001). The regression model was significant (F(2, 427) = 238.29, p < 0.001), with cultural adaptation stress (B = 0.11, SE = 0.01, β = 0.45, t = 11.98, p < 0.001) and social competence (B = -0.10, SE = 0.01, β = -0.41, t = -10.86, p < 0.001) as significant predictors, explaining 53% of the variance in hopelessness (R² = 0.53).Conclusion: The study demonstrates that cultural adaptation stress significantly increases hopelessness, while social competence serves as a protective factor reducing hopelessness among international students. These findings underscore the need for educational institutions to develop support systems that address cultural adaptation challenges and enhance social competence to promote the mental health and well-being of international students.